(untitled) (Fiep Bulletin - online, 2013)
The humanitycarries inits history meanings and picturesof bodiesthat were createdby companiesand enforcedthroughvariouscultures. Havingto analyze, interpret anddiscuss woman corporeality, from the historical deconstructionof the meaningsand pictures of bodiesand its variousdeterminants, including an education, we focus in thisexploratoryliterature, noting the embodimentunder the focusdialecticalandphenomenological.The meaningsand pictures constructedsomehowrepresentedan obstaclein overcomingprejudices, segmentationsandstigmatizingpatternsmarked in woman corporeality, making "Womanhood" victim ofdominationandsymbolic"slave" of industriesthat survivetheirexpense